PENGUKURAN TATA KELOLA TEKNOLOGI INFORMASI MENGGUNAKAN FRAMEWORK COBIT 5 DENGAN MODEL CAPABILITY LEVEL (Studi Kasus : Website Resmi Pemerintah Kota Tangerang Selatan) - Hasna Nabilah (2020)
To improve professional and transparent public services, the Department of Communication and Information (Diskominfo) of South Tangerang City seeks to realize the Mission of 5 South Tangerang City by creating and developing the Official Website of the South Tangerang City Government. So far, Diskominfo of South Tangerang City has never done an information system audit on the Website. In achieving the mission of South Tangerang City 5, the Official Website of the South Tangerang City Government as a manifestation of the implementation of public services must conduct a performance evaluation and evaluation to improve public services and improve good governance based on information technology. The measurement of IT governance uses the COBIT 5 framework. Researchers focus on measuring Capability Level in 2 domains namely the Evaluate, Direct and Monitor (EDM) domain and the Deliver, Service and Support (DSS) domain. From the results of the evaluation and measurement, a recommendation will be produced and the results of the assessment in this study as a whole are at level 1, therefore the recommendations given are further development in accordance with the organizational goals so that the Official Website of the Government of the City of South Tangerang can be optimized.